Prophet al-Khidr: Between the Quranic Text and Islamic Contexts: Oleh Irfan A. Omar - Khan, Khurshid (Asosiasi Teolog Indonesia, 2024)
A book review of Prophet al-Khidr: Between the Quranic Text and Islamic Contexts.